Effectiveness of Coretax Activation and Annual Tax Reporting on Taxpayer Compliance: Maslahah Mursalah Perspective: (Study at KP2KP Baradatu, Way Kanan, Lampung) - Adi Pancoko; Reynanda Destama; Ayu Baya Pratiwi; Tia Hidayanti (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to analyze the effectiveness of Coretax activation services and Annual Tax Return (SPT) reporting in improving taxpayer compliance, identify supporting and inhibiting factors, and examine their implementation from the perspective of maslahah mursalah. The research employs a qualitative approach with a field research design conducted at KP2KP Baradatu, Way Kanan, Lampung. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that Coretax activation services and Annual SPT reporting have provided convenience, efficiency, and flexibility for taxpayers, thereby contributing to improved compliance. Supporting factors include staff competence, availability of digital systems, and increasing taxpayer awareness, while inhibiting factors consist of low digital literacy, limited infrastructure, and resistance to change. From the perspective of maslahah mursalah, digital tax services reflect efforts to achieve public benefit, particularly in terms of convenience and public welfare, although not yet fully optimal. Therefore, strengthening education, service quality, and infrastructure is necessary to achieve more equitable public benefit.